Geographical drivers and climate-linked dynamics of Lassa fever in Nigeria - David W. Redding; Rory Gibb; Chioma C. Dan-Nwafor; Elsie A. Ilori; Rimamdeyati Usman Yashe; Saliu H. Oladele; Michael O. Amedu; Akanimo Iniobong; Lauren A. Attfield; Christl A. Donnelly; Ibrahim Abubakar; Kate E. Jones; et al. (Nature Communications, 2021)
Lassa Fever is a rodent-borne viral haemorrhagic fever that is a public health problem in West Africa. Here, the authors develop a spatiotemporal model of the socioecological drivers of disease using surveillance data from Nigeria, and find evidence of climate sensitivity.